Optimisation of microwave system for rice treatment - Nik Ismail, Nik Mohd Asri (2014)
Microwave heating has a potential to disinfest insect in rice grain. This method can be an alternative and a safe method to replace the current used of fumigant. Microwave leaves no chemical residue to hazard human health and safe for environment. A microwave system were developed using domestic microwave oven, an Arduino microcontroller, a switching circuit to study the effect of microwave energy applied to the infested rice grain. The microwave frequency used in the study is a standard 2.45MHz magnetron. The microcontroller is programmed to maintain the temperature at 55 – 65 ºC and duration is set at 2 – 3 mins. The experiments were carried out to monitor the effect of microwave on spawning process and the mortality of adult insect. There are two samples with and without microwave are stored at room temperature to monitor the activity of insect periodically. From the study, it was found that the use of microwave system gives positive result on the rice treatment where the effect caused the insect and eggs colonies activities reduced.